Effect of Return On Assets And Current Ratio on EPS in The Financial Report Disclosure - Cindy Aryani; Arfan Ikhsan (Asosiasi Dosen Akuntansi Indonesia, 2026)
This research intends to examine the impact of Return on Assets (ROA) and Current Ratio (CR) on Earnings Per Share (EPS) at PT Astra International Tbk throughout the 2003–2024 timeframe. EPS serves as a crucial measure of a company's profitability and is commonly utilized by investors to assess organizational performance. ROA indicates operational effectiveness, whereas CR assesses short-term liquidity. This study employs a quantitative approach utilizing secondary data obtained from PT Astra's audited financial reports, which are analyzed through multiple linear regression. The findings demonstrate that ROA has a significant and positive impact on EPS (regression coefficient = 12,929.077; p-value < 0.05), suggesting that efficient asset management notably improves earnings, thus validating H1. In the meantime, CR indicates no meaningful effect on EPS (p-value = 0.996), resulting in the dismissal of H2. The R-squared value of the model is 0.204, indicating that 20.4% of the variance in EPS is accounted for by ROA and CR, implying that additional variables also affect EPS and should be examined in future studies. These results highlight that operational efficiency is more significant than liquidity in influencing firm profitability, especially regarding PT Astra International Tbk in the timeframe of 2003–2024.